2016
DOI: 10.1158/0008-5472.can-15-1142
|View full text |Cite
|
Sign up to set email alerts
|

Calreticulin Expression in Human Non–Small Cell Lung Cancers Correlates with Increased Accumulation of Antitumor Immune Cells and Favorable Prognosis

Abstract: A high density of tumor-infiltrating mature dendritic cells (DC) and CD8þ T cells correlates with a positive prognosis in a majority of human cancers. The recruitment of activated lymphocytes to the tumor microenvironment, primed to recognize tumor-associated antigens, can occur in response to immunogenic cell death (ICD) of tumor cells. ICD is characterized by the preapoptotic translocation of calreticulin (CRT) from the endoplasmic reticulum (ER) to the cell surface as a result of an ER stress response accom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
123
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 165 publications
(128 citation statements)
references
References 48 publications
5
123
0
Order By: Relevance
“…17,[27][28][29] Antigen retrieval was performed by incubating slides in citrate buffer (pH 7.3) for 20 min at 98 C and cooling them for 30 min, at room temperature (RT). The sections were mounted on Shandon Sequenza coverplates (Thermo Fisher Scientific, 72-199-50) in distilled water.…”
Section: Phospho-eif2amentioning
confidence: 99%
“…17,[27][28][29] Antigen retrieval was performed by incubating slides in citrate buffer (pH 7.3) for 20 min at 98 C and cooling them for 30 min, at room temperature (RT). The sections were mounted on Shandon Sequenza coverplates (Thermo Fisher Scientific, 72-199-50) in distilled water.…”
Section: Phospho-eif2amentioning
confidence: 99%
“…21 In particular, CRT levels or exposure has been shown to convey robust prognostic information in subjects with multiple solid tumors, including neuroblastoma, non-small cell lung carcinoma, ovarian cancer, and colorectal carcinoma. [22][23][24][25] However, little is known on the prognostic value of CRT in patients with hematological malignancies, irrespective of the fact that these patients often receive ICD inducers, including anthracyclines and bortezomib. In a preliminary study, we reported that malignant blasts from patients with acute myeloid leukemia (AML) may expose CRT on the plasma membrane regardless of chemotherapy, 26 but did not investigate the prognostic relevance of these findings.…”
Section: Introductionmentioning
confidence: 99%
“…There are two striking differences between our prior work (on primary breast and lung cancer samples) and the present study (on melanoma metastases), although all these cancer types appear to be under strong immunosurveillance, meaning that the presence of an immune infiltrate and, more so, favorable ratios between immune effectors and immunosuppressive cell types predict improved OS. 21,31,[33][34][35][36][37][38][39]28 First, none of the malignant cell stress-related biomarkers had any impact on melanoma patient survival, contrasting with the observation that the presence of LC3B puncta and high expression of HMGB1 has a positive effect on the life expectancy of breast cancer patients. 23 This discrepancy might be related to the stage of patients (operable breast cancer vs. stage III/IV melanoma), intrinsic biological differences between neoplasias (perhaps related to the epithelial vs. neuroectodermal origin of these tumor types), or a rather distinct organization of the immunosurveillance system.…”
Section: Discussionmentioning
confidence: 93%
“…23,25 Reduced expression of CALR by cancer cells has been correlated with poor prognosis and reduced infiltration by CTL in colorectal cancer, 26 as well as in non-small cell lung cancer (NSCLC). 27,28 Similarly, low phosphorylation of eIF2a, which can be measured by immunohistochemistry using a phospho-neoepitope-specific antibody, predicts poor local immune responses and dismal prognosis in NSCLC. 28 In breast cancer, eIF2a phosphorylation could be associated with an increased ploidy (which induces ER stress and correlates with an increase in nuclear size) and the CD8 C…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation